Incidental Detection of Maternal Neoplasia in Noninvasive Prenatal Testing. (1st February 2018) - Dharajiya, Nilesh G; Grosu, Daniel S; Farkas, Daniel H; McCullough, Ron M; Almasri, Eyad; Sun, Youting; Kim, Sung K; Jensen, Taylor J; Saldivar, Juan-Sebastian; Topol, Eric J; van den Boom, Dirk; Ehrich, Mathias
Abstract: BACKGROUND: Noninvasive prenatal testing (NIPT) uses cell-free DNA (cfDNA) as an analyte to detect copy-number alterations in the fetal genome. Because maternal and fetal cfDNA contributions are comingled, changes in the maternal genome can manifest as abnormal NIPT results. Circulating tumor DNA (ctDNA) present in cases of maternal neoplasia has the potential to distort the NIPT readout to a degree that prevents interpretation, resulting in a nonreportable test result for fetal aneuploidy. METHODS: NIPT cases that showed a distortion from normal euploid genomic representation were communicated to the caregiving physician as nonreportable for fetal aneuploidy. Follow-up information was subsequently collected for these cases. More than 450000 pregnant patients who submitted samples for clinical laboratory testing >3 years are summarized. Additionally, in-depth analysis was performed for >79000 research-consented samples. RESULTS: In total, 55 nonreportable NIPT cases with altered genomic profiles were cataloged. Of these, 43 had additional information available to enable follow-up. A maternal neoplasm was confirmed in 40 of these cases: 18 malignant, 20 benign uterine fibroids, and 2 with radiological confirmation but without pathological classification. CONCLUSIONS: In a population of pregnant women who submitted a blood sample for cfDNA testing, an abnormal genomic profile not consistent with fetal abnormalities was detected in about 10 out of 100000 cases. A subset of these observations (18 of 43; 41.9%) was attributed to maternal malignant neoplasms. These observational results suggest the need for a controlled trial to evaluate the potential of using cfDNA as an early biomarker of cancer.